Correlation between serum vitamin D levels with severity of community acquired Pneumonia in hospitalized patients over sixty years old in Indonesia - Febrian, Marwan; Sudarso, Agus; Ilyas, Muhammad; Bakri, Syakib; Makbul Aman, Andi; Seweng, Arifin (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Old-aged persons commonly experience vitamin D deficiency due to many factors such as insufficient vitamin D intake, multiple medications, low sun exposure, and chronic kidney disease, thus increases susceptibility to infections. Community Acquired Pneumonia (CAP) is common in old-aged persons with a high morbidity rate. Its mortality rates can even reach 50-70% if accompanied by comorbidities. This study aimed to describe the correlation between CAP severity with serum vitamin D levels in hospitalized old-aged patients. Methods: This is an observational study with cross-sectional design, involving 82 hospitalized old-aged patients with diagnosis of CAP. Blood samples was collected in order to measure serum Vitamin D levels. Data normality was tested with Kolmogorov-Smirnov test, while Chi Square and Mann-Whitney test was utilized for statistical analysis. Statistical significance was described as p value < 0.05. Results: Average serum vitamin D levels were significantly lower in severe patients than in non-severe groups (p